Balance Report Prosperous Motorcycle Workshop - Maghfirani, Nazla Aqira (Indonesian Operations Research Association (IORA), 2021)
Based on the number of invoices or order notes, Bengkel Sejahtera experienced a decrease in service intensity in 2021 compared to the service intensity in 2020 which was quite high. This is because the workshop had experienced changes in service and financial management so that it could affect the company's financial condition. Therefore, the Bengkel Sejahtera balance sheet has been prepared to analyze financial statements using the current ratio or liquidity ratio and common size analysis, so that an overview of the company's financial position can be obtained. The research method used is a quantitative method with an explanatory research type. Data collection techniques were carried out by interviewing the company manager. The results of the analysis show that Bengkel Sejahtera has generated declining cash in 2021 with a ratio of 1:10 cash in 2020. In addition, the number of liabilities held has not been able to be fulfilled with company assets/assets due to the large number of passive funds that continue to be left to settle without being disbursed for fulfill the company's obligations. The financial statement analysis of Bengkel Sejahtera can be used by managers for better financial management, in which the management can begin to concentrate on the company's debts or obligations and not allow passive funds to continue to settle.